2010
DOI: 10.1371/journal.pone.0015373
|View full text |Cite
|
Sign up to set email alerts
|

Local Induction of Immunosuppressive CD8+ T Cells in the Gut-Associated Lymphoid Tissues

Abstract: BackgroundIn contrast to intestinal CD4+ regulatory T cells (Tregs), the generation and function of immunomodulatory intestinal CD8+ T cells is less well defined. To dissect the immunologic mechanisms of CD8+ T cell function in the mucosa, reactivity against hemagglutinin (HA) expressed in intestinal epithelial cells of mice bearing a MHC class-I-restricted T-cell-receptor specific for HA was studied.Methodology and Principal FindingsHA-specific CD8+ T cells were isolated from gut-associated tissues and phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…Furthermore, adoptive transfer of induced CD8 1 Foxp3 1 T cells did not ameliorate disease in an OVA-based allergic airway inflammation model (data not shown). Previous studies have reported the suppressive capacity of TGF-b-induced CD8 1 T cells [17,31,34,38], which in principle does not contradict our data. First, several studies did not compare the strength of suppression to that of CD4 1 Tregs [31,34,38], which depend on Foxp3 [3].…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Furthermore, adoptive transfer of induced CD8 1 Foxp3 1 T cells did not ameliorate disease in an OVA-based allergic airway inflammation model (data not shown). Previous studies have reported the suppressive capacity of TGF-b-induced CD8 1 T cells [17,31,34,38], which in principle does not contradict our data. First, several studies did not compare the strength of suppression to that of CD4 1 Tregs [31,34,38], which depend on Foxp3 [3].…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies have reported the suppressive capacity of TGF-b-induced CD8 1 T cells [17,31,34,38], which in principle does not contradict our data. First, several studies did not compare the strength of suppression to that of CD4 1 Tregs [31,34,38], which depend on Foxp3 [3]. Second, suppressive CD8 1 T cells were isolated either based on CD25 expression [17] (also broadly up-regulated on activated Foxp3 À T cells, at least in the absence of IL-6), or were tested without further separation for suppressive function [31,38], thereby not allowing for discrimination between Foxp3 1 and Foxp3 À subsets.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Here, the most prominent population is CD8 + CD28 -and suppressive via IL-10 secretion [8]. Furthermore, the induction of CD8 + regulatory T cells through the stimulation of the T-cell receptor mostly leads to the expression of Foxp3 in these T cells [3,4,[9][10][11]. Most of the adaptive CD8 + regulatory T cells appear to suppress via a cell-contact-dependent mechanism.…”
Section: Introductionmentioning
confidence: 99%